Possible Causes of and Measures to Minimise Risks of Abscesses Following DTP Vaccination - N. V. Tereshkina; I. I. Snegireva; M. A. Darmostukova (Безопасность и риск фармакотерапии, 2021)
Registration and analysis of adverse events following immunisation (AEFIs) allow for objective assessment and systematisation of AEFI causes, and promotion of vaccination safety. Development of abscesses after DTP vaccination is a fairly common AEFI, however, they are not included in the “Side effects” part of the patient information leaflet of the vaccine. The aim of the study was to analyse reasons for abscess development after DTP vaccination and to elaborate recommendations on enhancing the vaccine safety. The review of literature data, solicited reports on AEFIs, and AEFI investigation reports submitted to the Scientific Centre for Expert Evaluation of Medicinal Products during 2014–2018 suggests that abscesses associated with DTP vaccination may be caused by the vaccine reactogenicity, quality defects arising during production or distribution, and vaccine administration errors by healthcare personnel. Lack of information in the documents submitted by medical institutions does not allow to rule out any of the identified reasons. The minimisation of risks of abscesses requires quality control of DTP vaccines, maintenance of the cold chain during transportation and storage, and compliance with aseptic regulations during administration. Additional pharmacovigilance measures will also help enhance vaccination safety: improvement and standardisation of data collection during investigation of abscess development in the post-vaccination period, obligatory inclusion of data on the thickness of children’s subcutaneous adipose tissue (weight, body mass index) and the length of the needle used for vaccination in AEFI investigation reports. It is advisable to add information on abscess risk in the “Side effects” part of the patient information leaflet of the DTP vaccine, and to update the “Dosage regimen and administration route” and “Precautions” parts in order to minimise the risk. Personnel of healthcare facilities performing vaccination should be made aware of the importance of providing detailed data on AEFIs for subsequent objective analysis.